WAYS TO INCREASE NATIONAL EXPORT COMPETITIVENESS IN THE DEVELOPMENT OF FOREIGN TRADE (ON THE EXAMPLE OF AGRICULTURAL PRODUCTS) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Uzbekistan's agricultural sector holds significant potential in driving national economic development through increased foreign trade. However, challenges such as outdated infrastructure, limited product diversification, and restricted access to global markets continue to hinder export competitiveness. This article explores the current state of Uzbekistan’s agricultural exports and proposes practical strategies for enhancing competitiveness. Emphasis is placed on technological modernization, quality improvements, trade agreements, financing tools, and human capital development. Strengthening these areas will not only diversify Uzbekistan’s export structure but also ensure its sustainable integration into the global economy.